Transformasi Ekonomi Islam Melalui Solusi Fintech Digital : Jalan Menuju Pertumbuhan Berkelanjutan - Nunung Sinta Nuriyah; Aunur Rahmah Faqiyah Muchtar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The background of this research is that the transformation of the global economy has encouraged innovation in various sectors, including the Islamic economic sector in recent decades. The emergence of digital financial technology (FinTech) has provided new opportunities for the Islamic economy to encourage inclusive and sustainable growth. This research uses a literature study research method by reviewing and analyzing several journals that are closely related to the topic of discussion. This literature study approach involves collecting, evaluating, and analyzing various relevant literature sources to understand the interrelationship between the Islamic economy, digital fintech innovation, and sustainability principles. The result of this study is that the role of technology in supporting halal transactions includes technology can be an effective tool to increase awareness and understanding of Islamic financial principles, technology can be used as a campaign site to spread information about Islamic economics through interesting and easy-to-understand content, technology can create websites that focus on Islamic economics, and financial transactions can become easier and more efficient. Islamic fintech utilizes technological advances to offer transparent, efficient, and secure financial services to the unbanked. In addition, Islamic fintech supports sustainability by following sharia principles that prohibit riba (interest), gharar (uncertainty), and encourage fair and transparent financing.